Time analysis for the IAAF World Championships London 2017 1.500 m Men's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s 1500 m final was held in the late evening of August 13th. The heats were held three days earlier on August 10th, with the semi-finals the following evening. In the three heats, the first six finishers qualified automatically, and the six fastest non-automatic qualifiers also progressed. There were two semi-finals; the first five in each qualified for the final automatically, along with the two fastest losers. The average speeds for each of the top eight athletes over every 100 m segment are included in this report, as well as a graph of each of these athletes` positions at each 100 m split. The split data were provided by SEIKO. The results of the final are shown. (Attention! registration on the IAAF site is required for downloading)